(untitled) (Research, Society and Development, 2020)
This article aims was to compare two sugarcane genotypes under elevated atmospheric carbon dioxide (CO2) concentration and soil water deficit, through an approach based on statistical analysis of plant growth multiple characteristics. For that, Pearson’s correlation, dissimilarity and principal components (PC) analysis were performed, of some parameters such as stem length (culm) and roots length, number of leaves, dry mass of plant tissues, among other characteristics. Biometric attributes have a positive and significant correlation with each other. However, the dry mass values ​​have a negative correlation with the other parameters, meaning, therefore, there is a growth reduction as there is also a decrease in plants water conditions subjected to stress. Based on the dissimilarity and PC analysis, observed that genotypes genetically diverge and the imposed environmental condition influences growth responses. This preliminary study is an indication that this approach is essential for understanding the variations between the sugarcane genotypes responses. In addition, is evident (due to divergence) that analyses about the physiological and molecular responses of these genotypes in this environmental condition will contribute to the identification of regulated biological processes and possible tolerance mechanisms.